Facilitators of adherence to the study pill in the FEM-PrEP clinical trial. - Amy Corneli; Brian Perry; Kawango Agot; Khatija Ahmed; Fulufhelo Malamatsho; Lut Van Damme (PLoS ONE, 2015)
INTRODUCTION:FEM-PrEP did not demonstrate a reduction in HIV acquisition because of low study pill adherence. Yet, plasma and intracellular drug concentrations indicated that some participants had evidence of recent pill use. We conducted a follow-up study to identify, among other topics, participants' reasons for taking the study pill. METHODS:Qualitative, semi-structured interviews (SSIs) were conducted with 88 FEM-PrEP participants. Participants were purposefully selected based on their adherence drug concentrations collected during FEM-PrEP and placed into three adherence interview groups: "high," "moderate," and "none/scarce." Participants in the high and moderate groups described reasons why they adhered most or some of the time, including factors that facilitated their adherence. Participants in all groups described what they believed made it possible for other FEM-PrEP participants to adhere. In addition, 224 FEM-PrEP participants reported on their reasons for taking the study pills through a quantitative, audio computer-assisted self-interview (ACASI). Thematic analysis and descriptive statistics were used to analyze the qualitative and quantitative data, respectively. RESULTS:Five themes were identified from the SSIs as facilitating factors of adherence: 1) participants' support for the research, 2) HIV risk reduction, 3) routine formation and use of tools, 4) adherence counseling, and 5) partner awareness and support. Participants described similar facilitators when they spoke about other participants' adherence. Among the 172 participants who reported in ACASI that they had taken a study pill, wanting to help answer the research question was the most frequently stated reason for taking the pills (94%, n = 161). We also found evidence of preventive misconception. CONCLUSIONS:Adherence was facilitated by personal motivations, such as risk reduction and interest in the research outcome, and by adherence strategies consisting of external cues, reminders, and support. These findings can inform future HIV prevention clinical trials and the rollout of effective antiretroviral-based HIV prevention technologies for women.